N-Alkylcarbazoles: homolog manipulating long-lived room-temperature phosphorescence. Issue 33 (14th August 2018) - Zhang, Zhenzhen; Tang, Liangliang; Fan, Xiaojing; Wang, Yanhui; Zhang, Kai; Sun, Qikun; Zhang, Haichang; Xue, Shanfeng; Yang, Wenjun
Abstract : The homolog effect was demonstrated to be a promising avenue to manipulate the RTP of organic luminophores. Abstract : The present pure organic room-temperature phosphorescence (RTP) materials are characterized by heterocyclic molecules containing heavy atoms and carbonyl or sulfonyl groups, and a corresponding great success has been achieved, but few efforts have been made to develop simple and ultralong pure organic RTP emitters without the above groups. Furthermore, homologs and isomers all have the most comparable molecular structure and are more favorable to both the optimization of material properties and the accumulation of structure–property relationships. In the current work, we design and synthesize a series of crystallizable N -alkylcarbazole homologs (C n ) to investigate their phosphorescence properties. It is found that these crystalline powders have ultralong phosphorescence lifetimes of up to 1.2–1.5 s at low temperature, but the RTP lifetimes ofC1, C2, andC5 are greatly shortened to 0.4–0.6 s even under degas. In ambient air, the RTP lifetimes ofC1, C2 andC5 are further decreased to 200, 23 and 12 ms, respectively, indicating the strong temperature and oxygen sensitivity. In contrast, C3 andC4 can still maintain long RTP lifetimes up to 0.81 and 0.49 s in air, respectively, affording excellent RTP emitters. Single crystal analyses and theoretical calculations reveal that the alkyl chain can affect molecular packing and intersystem crossing, and this work demonstrates that the homolog effect is a useful avenue in manipulating RTP properties and the ambient sensitivity.